Movember GAP1 PDX project: An international collection of serially transplantable prostate cancer patient‐derived xenograft (PDX) models. Issue 16 (2nd August 2018) - Navone, Nora M.; van Weerden, Wytske M.; Vessella, Robert L.; Williams, Elizabeth D.; Wang, Yuzhuo; Isaacs, John T.; Nguyen, Holly M.; Culig, Zoran; van der Pluijm, Gabri; Rentsch, Cyril A.; Marques, Rute B.; de Ridder, Corrina M. A.; et al.
Abstract : Background: While it has been challenging to establish prostate cancer patient‐derived xenografts (PDXs), with a take rate of 10‐40% and long latency time, multiple groups throughout the world have developed methods for the successful establishment of serially transplantable human prostate cancer PDXs using a variety of immune deficient mice. In 2014, the Movember Foundation launched a Global Action Plan 1 (GAP1) project to support an international collaborative prostate cancer PDX program involving eleven groups. Between these Movember consortium members, a total of 98 authenticated human prostate cancer PDXs were available for characterization. Eighty three of these were derived directly from patient material, and 15 were derived as variants of patient‐derived material via serial passage in androgen deprived hosts. A major goal of the Movember GAP1 PDX project was to provide the prostate cancer research community with a summary of both the basic characteristics of the 98 available authenticated serially transplantable human prostate cancer PDX models and the appropriate contact information for collaborations. Herein, we report a summary of these PDX models. Methods: PDX models were established in immunocompromised mice via subcutaneous or subrenal‐capsule implantation. Dual‐label species (ie, human vs mouse) specific centromere and telomere Fluorescence In Situ Hybridization (FISH) and immuno‐histochemical (IHC) staining of tissue microarrays (TMAs) containing replicates of the PDX models were used for characterization of expression of a number of phenotypic markers important for prostate cancer including AR (assessed by IHC and FISH), Ki67, vimentin, RB1, P‐Akt, chromogranin A (CgA), p53, ERG, PTEN, PSMA, and epithelial cytokeratins. Results: Within this series of PDX models, the full spectrum of clinical disease stages is represented, including androgen‐sensitive and castration‐resistant primary and metastatic prostate adenocarcinomas as well as prostate carcinomas with neuroendocrine differentiation. The annotated clinical characteristics of these PDXs were correlated with their marker expression profile. Conclusion: Our results demonstrate the clinical relevance of this series of PDXs as a platform for both basic science studies and therapeutic discovery/drug development. The present report provides the prostate cancer community with a summary of the basic characteristics and a contact information for collaborations using these models.